How Will Sea Ice Loss Affect the Greenland Ice Sheet? - Pausata, Francesco S. R.; LeGrande, Allegra; Roberts, William (Eos, 2016)
On the Puzzling Features of Greenland Ice-Core Isotopic Composition; Copenhagen, Denmark, 26–28 October 2015

Deglacial Indian monsoon failure and North Atlantic stadials linked by Indian Ocean surface cooling - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter (Nature Geoscience, 2016)

ENSO response to high‐latitude volcanic eruptions in the Northern Hemisphere: The role of the initial conditions - Pausata, Francesco S. R.; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2016)
Abstract A large ensemble of Earth System Model simulations is analyzed to show that high‐latitude Northern Hemisphere eruptions give rise to El Niño‐like anomalies in the winter following the eruption, the amplitude of which depends on the state of the tropical Pacific at the time of the eruption. The El Niño‐like anomalies are almost three times larger when the eruption occurs during an incipient La Niña or during a neutral state compared to an incipient El Niño. The differential response results from stronger atmosphere‐ocean coupling and extra‐tropical feedbacks during an incipient La Niña compared to El Niño. Differences in the response continue through the second and third years following the eruption. When the eruption happens in a year of an incipient El Niño, a large cold (La Niña‐like) anomaly develops in year 2; if the eruption occurs in a year of an incipient La Niña, no anomalies are simulated in year 2 and a La Niña‐like response appears in year 3. After the El Niño‐like anomaly in the first winter, the overall tendency of ENSO in the following 2 years is toward a La Niña state. Our results highlight the high sensitivity of tropical Pacific dynamics under volcanic forcing to the ENSO initial state and lay the groundwork for improved predictions of the global climatic response to high‐latitude volcanic eruptions. , Key Points HL eruptions alter the mean state of ENSO, and detectable anomalies are seen up to 3 years after the eruption Stronger El Niño‐like anomalies on year 1 when eruptions occurs under developing La Niñas La Niña‐like anomalies on year 2 and year 3 when eruptions occurs under developing El Niños and La Niñas, respectively

Climate effects of a hypothetical regional nuclear war: Sensitivity to emission duration and particle composition - Pausata, Francesco S. R.; Lindvall, Jenny; Ekman, Annica M. L.; Svensson, Gunilla (Earth's Future, 2016)
Abstract Here, we use a coupled atmospheric‐ocean‐aerosol model to investigate the plume development and climate effects of the smoke generated by fires following a regional nuclear war between emerging third‐world nuclear powers. We simulate a standard scenario where 5 Tg of black carbon ( BC ) is emitted over 1 day in the upper troposphere–lower stratosphere. However, it is likely that the emissions from the fires ignited by bomb detonations include a substantial amount of particulate organic matter ( POM ) and that they last more than 1 day. We therefore test the sensitivity of the aerosol plume and climate system to the BC / POM ratio (1:3, 1:9) and to the emission length (1 day, 1 week, 1 month). We find that in general, an emission length of 1 month substantially reduces the cooling compared to the 1‐day case, whereas taking into account POM emissions notably increases the cooling and the reduction of precipitation associated with the nuclear war during the first year following the detonation. Accounting for POM emissions increases the particle size in the short‐emission‐length scenarios (1 day/1 week), reducing the residence time of the injected particle. While the initial cooling is more intense when including POM emission, the long‐lasting effects, while still large, may be less extreme compared to the BC ‐only case. Our study highlights that the emission altitude reached by the plume is sensitive to both the particle type emitted by the fires and the emission duration. Consequently, the climate effects of a nuclear war are strongly dependent on these parameters. , Key Points Importance of including OC when simulating nuclear wars Importance of the fire emission length when simulating nuclear wars

Sources of Sahelian‐Sudan moisture: Insights from a moisture‐tracing atmospheric model - Salih, Abubakr A. M.; Zhang, Qiong; Pausata, Francesco S. R.; Tjernström, Michael (Journal of Geophysical Research: Atmospheres, 2016)
Abstract The summer rainfall across Sahelian‐Sudan is one of the main sources of water for agriculture, human, and animal needs. However, the rainfall is characterized by large interannual variability, which has attracted extensive scientific efforts to understand it. This study attempts to identify the source regions that contribute to the Sahelian‐Sudan moisture budget during July through September. We have used an atmospheric general circulation model with an embedded moisture‐tracing module (Community Atmosphere Model version 3), forced by observed (1979–2013) sea‐surface temperatures. The result suggests that about 40% of the moisture comes with the moisture flow associated with the seasonal migration of the Intertropical Convergence Zone (ITCZ) and originates from Guinea Coast, central Africa, and the Western Sahel. The Mediterranean Sea, Arabian Peninsula, and South Indian Ocean regions account for 10.2%, 8.1%, and 6.4%, respectively. Local evaporation and the rest of the globe supply the region with 20.3% and 13.2%, respectively. We also compared the result from this study to a previous analysis that used the Lagrangian model FLEXPART forced by ERA‐Interim. The two approaches differ when comparing individual regions, but are in better agreement when neighboring regions of similar atmospheric flow features are grouped together. Interannual variability with the rainfall over the region is highly correlated with contributions from regions that are associated with the ITCZ movement, which is in turn linked to the Atlantic Multidecadal Oscillation. Our result is expected to provide insights for the effort on seasonal forecasting of the rainy season over Sahelian Sudan. , Key Points The moisture associated with ITCZ flow accounts for about 40%‐50% of the precipitated water The local evaporation provides about 20% of the precipitated water The multiyear variability in the rainfall seems to be linked to the AMO

The Model Intercomparison Project on the climatic response toVolcanic forcing (VolMIP): experimental design and forcing input data for CMIP6 - Zanchettin, Davide; Khodri, Myriam; Timmreck, Claudia; Toohey, Matthew; Schmidt, Anja; Gerber, Edwin P.; Hegerl, Gabriele; Robock, Alan; Pausata, Francesco S. R.; Ball, William T.; Bauer, Susanne E.; Bekki, Slimane; et al. (Geoscientific Model Development, 2016)
Abstract. The enhancement of the stratospheric aerosol layer by volcanic eruptions induces a complex set of responses causing global and regional climate effects on a broad range of timescales. Uncertainties exist regarding the climatic response to strong volcanic forcing identified in coupled climate simulations that contributed to the fifth phase of the Coupled Model Intercomparison Project (CMIP5). In order to better understand the sources of these model diversities, the Model Intercomparison Project on the climatic response to Volcanic forcing (VolMIP) has defined a coordinated set of idealized volcanic perturbation experiments to be carried out in alignment with the CMIP6 protocol. VolMIP provides a common stratospheric aerosol data set for each experiment to minimize differences in the applied volcanic forcing. It defines a set of initial conditions to assess how internal climate variability contributes to determining the response. VolMIP will assess to what extent volcanically forced responses of the coupled ocean–atmosphere system are robustly simulated by state-of-the-art coupled climate models and identify the causes that limit robust simulated behavior, especially differences in the treatment of physical processes. This paper illustrates the design of the idealized volcanic perturbation experiments in the VolMIP protocol and describes the common aerosol forcing input data sets to be used.